THE EIGHTH GRADE STUDENTS’ ERRORS OF SMP NEGERI 6 LHOKSUKON ACEH UTARA IN WRITING NARRATIVE TEXT - Sariakin Sariakin; Teuku Mahmud (Jurnal Sosial Humaniora Sigli, 2022)
The aims of the study is to find out the kinds of errors are made by the seventh grade students of SMP Negeri 6 Lhoksukon Aceh Utara in writing narrative text and  the  most  dominant  error  made  by  the seventh grade students of SMP Negeri 6 Lhoksukon Aceh Utara in writing narrative text. The researcher applied descriptive research. The researcher describes students’ errors in writing recount text.  Therefore this research belongs to qualitative research because only describes the students’ errors in writing narrative text. The population of the research  is the whole students of the eighth grade in academic year of 2021/2022. The total amount of population is around 120 students. Meanwhile the sample of this research is the students who are taken from class VIII1 and VIII2and the total sample is 60.  Based on the finding in this research, there are 150 errors made by the students of SMP Negeri 6 Lhoksukon in writing narrative text. The errors   are classified  as  follows:  (1)  error  content  which  consists  of  (a) orientation = 17 errors, (b) events = 26 errors, (c) reorientations = 19 errors, and the total errors are 62; (2) errors in vocabulary = 15 errors, (3) errors in grammar =  51 errors, and, (4) errors in mechanics = 20 errors. Errors in content of narrative text are 62 items 42 %. Errors in vocabulary are 15 items or 10%. The occurrence of errors in grammar are 51 or 34%. Meanwhile, errors in mechanic are 20 is or .  are 14%.Key Words: Students’ Errors, Writing Narrative Text